2008
DOI: 10.1111/j.1399-5618.2008.00638.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological and electrophysiological indices of neurocognitive dysfunction in bipolar II disorder

Abstract: The functional significance of neuropsychological impairment is discussed. Differences regarding some aspects of executive function may be related to psychomotor speed, and not primarily to dysexecutive functioning. ERP results must be interpreted with caution, but the differences found in MMN latency and amplitudes may be related to fronto-temporal circuitry underlying pre-attentive stimulus change detection as measured by MMN, and are discussed in relation to previous research on MMN in other neuropsychiatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 54 publications
8
71
0
Order By: Relevance
“…However, the sample size of BD II patients in these two studies was relatively small. Noteworthy, also, is the study by Andersson et al (2008), where performance of BD II patients was significantly worse than that of HCs on all measures, except for phonemic verbal fluency. These authors discussed the functional significance of neuropsychological impairment and suggested that differences regarding some aspects of executive function may be related to psychomotor speed, and not primarily to dysexecutive functioning, taking into consideration their findings in electrophysiological index.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the sample size of BD II patients in these two studies was relatively small. Noteworthy, also, is the study by Andersson et al (2008), where performance of BD II patients was significantly worse than that of HCs on all measures, except for phonemic verbal fluency. These authors discussed the functional significance of neuropsychological impairment and suggested that differences regarding some aspects of executive function may be related to psychomotor speed, and not primarily to dysexecutive functioning, taking into consideration their findings in electrophysiological index.…”
Section: Discussionmentioning
confidence: 97%
“…Three out of four studies found that BD II participants had a significantly poorer performance than the HC group Andersson et al 2008 ;Simonsen et al 2008). In one of them, both BD I and BD II groups did not differ significantly among each other (Simonsen et al 2008) and in another the BD II patients showed an intermediate level of performance between the BD I and control group .…”
Section: Inhibitory Controlmentioning
confidence: 99%
“…The authors suggested that P300, but not MMN, was a valid endophenotype, albeit with limited specificity. In contrast, Andersson and colleagues 26 found that patients with bipolar II disorder had decreased frontal MMN in the absence of a P300 impairment (although they reported a delayed P3a for female patients). Given such contrasting findings and questions surrounding the specificity of MMN and P300 (and P3a), there is a need to further explore these biomarkers in patients with bipolar disorder.…”
Section: Introductionmentioning
confidence: 85%
“…The neural mechanisms underlying disturbances in cognitive functions are poorly understood, and they may be present even at the level of automatic information processing (for a review, see Beck, 2008). Therefore several studies used aMMN (or its magnetic counterpart, MMNm) to study automatic sensorycognitive processes in depression (Iv, Zhao, Gong, Chen, & Miao, 2010;K€ ahk€ onen et al, 2007;Lepist€ o et al, 2004;Pang et al, 2014;Takei et al, 2009) and BP (Andersson, Barder, Hellvin, Løvdahl, & Malt, 2008;Takei et al, 2010). Takei et al applied magnetoencephalography to measure information processing deficit in depression (2009) andBP (2010).…”
Section: Mood Disordersmentioning
confidence: 99%